The study of motivational factors of entrepreneurs in the Singapore used car industry. - Lim, Bee Lan. (2008)
The purpose of this project is to identify the factors that motivate an individual to start a business in the Singapore used car industry. The Singapore used car industry is chosen because it is one of the most established industries in Singapore. Problems unique to the used car industry are identified and recommendations are made to further encourage and stimulate entrepreneurship in this industry. The effects of the regional economic crisis on this industry will also be examined.